Intrapreneurship and expectations restrictions (Dimensión Empresarial, 2020)
This article develops arguments about the factors that promote intrapreneurship in relation to role theory. These are based on contributions from interactional and structural sociology. Fixed theoretical tools for intrapreneurship are not enough. So, the structural and interactionist perspective of sociology is necessary to understand the concept of intrapreneurship. The above approaches depend on individuals, organizations or environments to encourage potential employees to be intrapreneurs. Thus, Expectations can be a cornerstone for intrapreneurship because intrapreneurs learn from their roles.